(3fRgg GdfGXQ aj hVY NWhW aVd GdOGFQs - (3eMeO Hf CHi GdaJM GdUhai,J (B950 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLg (B: (3adeG cGf Yde GdhbJ ef Ydhe GdOjf GdhGLHg Ydi Gdecdajf s
(3BNQgG (B:s
(3ChVMfG Pdc ai QSGdJfG GdcHQi GdeSeGg HGdOQ GdeJfGKQ ai QSe NWhW aVd GdOGFQ s
(3Cdag Sfg (B878(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B116s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B159 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B106 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1948s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B196) s
Keywords: (3Gdadcs